2017
DOI: 10.1038/ncomms16170
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Directly converting CO2 into a gasoline fuel

Abstract: This Article contains an error in Fig. 3; in that, 'Fe 3 C 4 ' in the orange semi-ellipse should be 'Fe 3 O 4 '.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…3a ), indicating that the RWGS reaction is enhanced under the conditions with a higher partial pressure of H 2 . This is different from the common observation, i.e., a lower selectivity of CO at a higher feed H 2 /CO 2 ratio, over traditional oxide catalysts for the hydrogenation of CO 2 to methanol 22 , gasoline fuel 23 or aromatics 24 , which is explained as the secondary hydrogenation of CO. To find out the reason, the hydrogenation of CO was comparatively studied over GaN with different crystal sizes (Fig. 5 ).…”
Section: Resultscontrasting
confidence: 92%
“…3a ), indicating that the RWGS reaction is enhanced under the conditions with a higher partial pressure of H 2 . This is different from the common observation, i.e., a lower selectivity of CO at a higher feed H 2 /CO 2 ratio, over traditional oxide catalysts for the hydrogenation of CO 2 to methanol 22 , gasoline fuel 23 or aromatics 24 , which is explained as the secondary hydrogenation of CO. To find out the reason, the hydrogenation of CO was comparatively studied over GaN with different crystal sizes (Fig. 5 ).…”
Section: Resultscontrasting
confidence: 92%
“…When 6.25Cu–Fe 2 O 3 and HZSM-5-c were mixed in the powder form, a relatively low CO 2 conversion and aromatic selectivity were obtained; meanwhile, the undesired CH 4 was the dominant product. This is probably because the HZSM-5 acid site can easily poison the alkali site on the 6.25Cu–Fe 2 O 3 surface in such a short distance, further impeding the carburization and decreasing the surface basicity of the oxide catalyst. , It was found that CO 2 conversion, aromatics selectivity, and C 5+ hydrocarbon selectivity increased sharply to 57.3, 56.61, and 80.89%, respectively, but the selectivity of methane dropped to 10.48% correspondingly, when granule stacking was adopted in this composite catalyst. With this kind of integration manner, intermediates generated on the 6.25Cu–Fe 2 O 3 surface can efficiently diffuse to the pores of zeolites, and then, aromatization and oligomerization proceeded immediately to produce aromatics and long-chain hydrocarbons, thus facilitating the transformation of CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, high selectivity of CO (>44%) was also generated as a byproduct, with detrimental CO 2 conversion (<20%), , because of the temperature mismatch of methanol synthesis and aromatization . Similarly, the modified Fischer–Tropsch synthesis (FTS) route, which proceeds successively through CO 2 -FT [combination of reverse water-gas shift (RWGS) and FTS] and aromatization, was also widely explored, , and Fe-based catalysts are most intensively explored in CO 2 -FT, owing to its good performance in RWGS and FTS. Nevertheless, Fe-based/HZSM-5 catalysts usually exhibit lower aromatics selectivity and CO 2 conversion, probably because of the limitation on the Anderson–Schulz–Flory (ASF) law.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Wei et al reported a highly efficient, stable and multifunctional Na-Fe3O4/HZSM-5 catalytic system [107], for direct hydrogenation of CO2 to gasoline-range (C5-C11), in which the selectivity of C5-C11 hydrocarbons reached 78% (based on total hydrocarbons), while under industrial conditions only reached 4% methane selectivity at a 22% CO2 conversion. Characterization by high resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), and Mossbauer spectroscopy showed that two different types of iron phase-i.e., Fe3O4 and x-Fe5C2-were discerned Zhang et al used an impregnation method to prepare Fe-Zn-K catalysts, in which K was used as a promoter [71].…”
Section: Co2 To Other Productsmentioning
confidence: 99%
“…Reaction scheme for CO2 hydrogenation to gasoline-range hydrocarbons, reproduced with permission from[107]. Copyright Nature Publishing Group, 2017.…”
mentioning
confidence: 99%